Delayed Umbilical Cord Clamping is Not Associated with Acute Kidney Injury in Very Low Birth Weight Neonates - Harer, Matthew W.; McAdams, Ryan M.; Conaway, Mark; Vergales, Brooke D.; Hyatt, Dylan M.; Charlton, Jennifer R. (American Journal of Perinatology, 2020)
Objective This study aimed to determine if delayed cord clamping (DCC) is associated with a reduction in neonatal acute kidney injury (AKI).Study Design A retrospective single-center cohort study of 278 very low birth weight (VLBW) neonates was performed to compare the incidence of AKI in the following groups: immediate cord clamping (ICC), DCC, and umbilical cord milking. AKI was diagnosed by the modified neonatal Kidney Diseases and Improving Global Outcomes (KDIGO) definition.Results The incidence of AKI in the first week was 20.1% with no difference between groups (p = 0.78). After adjustment for potential confounders, the odds of developing AKI, following DCC, compared with ICC was 0.93 (confidence interval [CI]: 0.46–1.86) with no reduction in the stage of AKI between groups.Conclusion In this study, DCC was not associated with a reduced rate of AKI in VLBW neonates. However, the data suggest that DCC is also not harmful to the kidneys, further supporting the safety of DCC in VLBW neonates.
Keywords: acute kidney injury; delayed cord clamping; umbilical cord milking; very low birth weight; premature; preterm birth; neonate